Kölbl, Julia; Orlova, Iryna & Wolf, Michaela (eds.) (2020): ¿Pasarán? Kommunikation im Spanischen Bürgerkrieg. Interacting in the Spanish Civil War. Vienna, Hamburg: new academic press. - Pym, Anthony (chronotopos – A Journal of Translation History, 2022)
A review of: Kölbl, Julia; Orlova, Iryna & Wolf, Michaela (eds.) (2020): ¿Pasarán? Kommunikation im Spanischen Bürgerkrieg. Interacting in the Spanish Civil War. Vienna, Hamburg: new academic press. 223 pp, ISBN 978-3-7003-2179-8.